PROGRAM PENGGEMUKAN TERNAK DOMBA EKOR GEMUK DI KECAMATAN SEMANDING, KABUPATEN TUBAN - Indah Norma Triana; Rr. Ratih Ratnasari; Ajik Azmijah (Jurnal Layanan Masyarakat (Journal of Public Services), 2017)
The program for fattening and breeding of fat-tailed sheep (EG) in Semanding District, Tuban Regency, was collaboration work among Institute for Research and Community Service (LPPM) of Universitas Airlangga, Gemah Ripah, and Mandiri’s Breeding Coomunity, Tuban Regency. The program was conducted by veterinarians, who are experts in animal reproduction, animal feeding and health, camping and its sanitation, assisted by local people. The activities included training on livestock breeding, demonstration of animal feeding and caging, vaccination, livestock maintenance at pre- and post-production, and also the health examination and treatment of sick fat-tailed sheep. There was also presentation about medicines used for animal fattening, i.e. Bio-N-Plus, Premix Minerals, and vitamin B-Complex. These drugs were given to the participants to accelerate the cattle growth. In addition, a simulation on how to breed fat-tailed sheep was also demonstrated to the participants. At the end of the program, a package was given to Gemah Ripah dan Mandiri’s Breeding Community. It consisted of six fat-tailed sheep, 3 quintals of concentrate feeds used for about four months feeding, the money for renovating the animal cages, vitamins, medicines, and vaccines. This training program was successfully increased the ability of participants, Gemah Ripah and Mandiri’s Breeding Coomunity, to breed the fat-tailed sheep in a relatively good way. It was supported by the facts that the cattle had increased body weights and there was no observed risk of sickness and animal death. AbstrakProgram penggemukan dan budidaya ternak domba ekor gemuk (EG) di Kecamatan Semanding, Kabupaten Tuban merupakan bentuk kerja sama antara Lembaga Pengabdian Kepada Masyarakat Universitas Airlangga dengan Kelompok Ternak Gemah Ripah dan Mandiri, Tuban. Pelaksanaan program ini melibatkan dokter hewan, yang merupakan ahli reproduksi, ahli pakan ternak, ahli kesehatan ternak serta ahli sanitasi dan perkandangan, serta dibantu oleh tenaga lokal. Kegiatan yang dilakukan antara lain meliputi: pelatihan budidaya ternak domba EG, peragaan pembuatan pakan dan kandang, pemberian vaksin, pemeliharaan pra- dan pasca- produksi, serta pemeriksaan dan pengobatan domba yang sakit. Pada kesempatan ini, juga diperkenalkan obat untuk penggemukan domba, yaitu: Bio-N-Plus, Premix Mineral, dan vitamin B-Kompleks. Bahan tersebut diberikan dengan tujuan untuk mempercepat pertumbuhan domba. Selain itu, juga dilakukan simulasi beternak domba EG bagi para peternak. Pada akhir pelatihan telah diberikan paket ternak domba EG kepada kelompok peternak Gemah Ripah Dan Mandiri, yaitu berupa: 6 ekor domba EG, 3 kwintal pakan konsentrat yang bisa digunakan untuk empat bulan, biaya renovasi kandang domba EG, serta vitamin, obat-obatan, dan vaksin. Dari hasil pelaksanaan program ini, para peternak telah berhasil memelihara domba EG dengan cara yang lebih baik dengan tanda pertumbuhan berat badan ternak yang semakin meningkat, serta tidak ada resiko sakit dan kematian hewan ternak.